College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Section 2.8 - One-to-One Functions and their Inverses - 2.8 Exercises: 36

Answer

$f^{-1}(f^{-1}(0))$ = 4

Work Step by Step

First find where f(x) = 0. Since the function is one-to-one, f(5) = 0. Therefore $f^{-1}(f^{-1}(0))$ = $f^{-1}(5)$ Then find where f(x) = 5. Since the function is one-to-one, f(4) = 5. Therefore $f^{-1}(f^{-1}(0))$ = $f^{-1}(5)$ = 4
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.